Adaption, implementation and evaluation of collaborative service improvements in the testing and result communication process in primary care from patient and staff perspectives: A qualitative study - Litchfield, I.; Bentham, L.; Lilford, R.; McManus, R.; Hill, Anne-Marie; Greenfield, S. (BioMed Central, 2017)
Background: Increasing numbers of blood tests are being ordered in primary care settings and the swift and accurate communication of test results is central to providing high quality care. The process of testing and result communication is complex and reliant on the coordinated actions of care providers, external groups in laboratory and hospital settings, and patients. This fragmentation leaves it vulnerable to error and the need to improve an apparently fallible system is apparent. However, primary care is complex and does not necessarily adopt change in a linear and prescribed manner influenced by a range of factors relating to practice staff, patients and organisational factors. To account for these competing perspectives, we worked in conjunction with both staff and patients to develop and implement strategies intended to improve patient satisfaction and increase efficiency of existing processes. Methods: The study applied the principles of 'experience-based co-design' to identify key areas of weakness and source proposals for change from staff and patients. The study was undertaken within two primary practices situated in South Birmingham (UK) of contrasting size and socio-economic environment. Senior practice staff were involved in the refinement of the interventions for introduction. We conducted focus groups singly constituted of staff and patients at each practice to determine suitability, applicability and desirability alongside the practical implications of their introduction. Results: At each practice four of the six proposals for change were implemented these were increased access to phlebotomy, improved receptionist training, proactive communication of results, and increased patient awareness of the tests ordered and the means of their communication. All were received favourably by both patients and staff. The remaining issues around the management of telephone calls and the introduction of electronic alerts for missing results were not addressed due to constraints of time and available resources. Conclusions: Approaches to tackling the same area of weakness differed at practices and was determined by individual staff attitudes and by organisational and patient characteristics. The long-term impact of the changes requires further quantitative evaluation.